2022
DOI: 10.1016/j.ypmed.2021.106929
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of the COVID-19 pandemic on a population-based screening program for colorectal cancer in Catalonia (Spain)

Abstract: The COVID-19 pandemic caused the suspension at all levels of the Catalan FIT-based CRC screening program on March 12, 2020. Screening invitations to FIT were resumed on September 1, 2020. We aimed to assess the short-term impact of the pandemic and describe strategies implemented to minimize harm by the disruption of the FIT-based CRC screening in the Metropolitan Area of Barcelona. We analyzed participation rate, colonoscopy adherence, time intervals to colonoscopy, detection rates, and advanced-stage cancers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
1
23
1
Order By: Relevance
“…Invitations to the fecal immunochemical test (FIT) based colorectal cancer screening program resumed in September 2020, but ∼43% of the target population had not yet received their invitation by December 2020. Given that before the pandemic ∼11% of invasive colorectal cancers in Catalonia were detected by screening (unpublished data), the lower rates of participation, adherence to colonoscopy, and cancer detection due to the increased FIT positivity threshold during the pandemic 68 could explain why colorectal cancer diagnoses did not return to baseline levels until 6 months after reopening the screening program. The progressive increase in endoscopies and elective surgeries as the pandemic progressed probably helped the rebound in diagnosis of this cancer in all age groups, not only in the target age group of the colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Invitations to the fecal immunochemical test (FIT) based colorectal cancer screening program resumed in September 2020, but ∼43% of the target population had not yet received their invitation by December 2020. Given that before the pandemic ∼11% of invasive colorectal cancers in Catalonia were detected by screening (unpublished data), the lower rates of participation, adherence to colonoscopy, and cancer detection due to the increased FIT positivity threshold during the pandemic 68 could explain why colorectal cancer diagnoses did not return to baseline levels until 6 months after reopening the screening program. The progressive increase in endoscopies and elective surgeries as the pandemic progressed probably helped the rebound in diagnosis of this cancer in all age groups, not only in the target age group of the colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in DC compliance was also observed in other CRC screening programs [16][17][18]. Corely et al (2017) demonstrated that a DC after 10 months was associated with a higher CRC risk and more advanced-stage CRC compared to a DC at 8-30 days [4].…”
Section: Discussionmentioning
confidence: 83%
“…33, 34 In some studies, a shift to more advanced stages and different initial therapeutic approaches have been observed for breast cancer and colorectal cancers. 35 36 37 38 39 Investigating the impact on cancer stage is out of the scope of this study. Nevertheless, computing the expected delay cumulated up to now can give an estimate of the impact on mortality and, for cervical and colorectal cancer, on incidence.…”
Section: Discussionmentioning
confidence: 99%